2021
DOI: 10.15761/icst.1000358
|View full text |Cite
|
Sign up to set email alerts
|

Putative oncogenic viruses: Some data on Brazilian subjects

Abstract: The concepts of cancer etiology have changed over the years, mainly based on molecular epidemiology studies and bioinformatics approaches. Until relatively recently the most accepted theory of cancer etiology has dealt with the accumulation of gene mutations and the consequent cognate proteins dysfunction, but now some authors have argued against the proposed theory. The additional role of noncellular genes in the cause of malignancy, associated to environmental factors and host genetic background, has been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…It has been documented that viruses play a critical role in the development of a variety of human malignancies. Tenόrio et al [3] reviewed the impact of such oncogenic viruses, including human T-cell lymphotropic virus, human papillomavirus (HPV), mouse/human mammary tumor virus, human endogenous retrovirus (HERV), and hepatitis C virus. Interestingly, serological survey, using PCR-based assays, revealed that some of their patients with head and neck cancer were positive for HPV (1 of 38) and HERV-K (31 of 35).…”
mentioning
confidence: 99%
“…It has been documented that viruses play a critical role in the development of a variety of human malignancies. Tenόrio et al [3] reviewed the impact of such oncogenic viruses, including human T-cell lymphotropic virus, human papillomavirus (HPV), mouse/human mammary tumor virus, human endogenous retrovirus (HERV), and hepatitis C virus. Interestingly, serological survey, using PCR-based assays, revealed that some of their patients with head and neck cancer were positive for HPV (1 of 38) and HERV-K (31 of 35).…”
mentioning
confidence: 99%